Myths and facts of the utility death spiral. (November 2017) - Castaneda, Monica; Jimenez, Maritza; Zapata, Sebastian; Franco, Carlos J.; Dyner, Isaac
Abstract: As the electricity industry is changing worldwide, the swift expansion of basic forms of Distributed Generation (DG), particularly photovoltaic deployment, threatens the current utility business models that during the transitional stages may challenge the reliability of electricity systems and societal welfare. These findings are matters of major concern to policy makers as the shift towards more decentralized power systems must be sustainable, and although this brings great opportunities, it also pauses important challenges. The transition calls for policy and regulation attention. For some researchers, DG development should be accompanied with design changes to distribution tariffs, the addition of connection charge and modifications to Net Metering, while for others, certain of these measures could discourage DG investments. In this context and given multiple uncertainties, the authors propose a system dynamics model to examine the effect of the diffusion of Photovoltaic technology on the revenues of utilities and customers. The paper concludes that for the Colombian case, it is possible under certain conditions to attain a balance between social welfare and the aversion of the utility death spiral through systemic interventions. Highlights: Diffusion of solar PV is taking place in all electricity markets worldwide. Customers are benefiting from solar PV. In this context, the utility death spiral is a challenge. Systemic policy intervention facilitate sustainable PV diffusion.